2020
DOI: 10.1080/13504622.2020.1737647
|View full text |Cite
|
Sign up to set email alerts
|

Personal, professional, political: an exploration of science teacher identity development for teaching climate change

Abstract: for their expertise throughout the MADE CLEAR project. I also would like to express my appreciation to my MADE CLEAR colleagues on the Learning Sciences research team and K-12 professional development team for their collective guidance and moral support: Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 135 publications
0
0
0
Order By: Relevance
“…These tensions and difficulties are also found in a more recent study of US-based high school science teachers who taught climate change using ESE-informed approaches [15]. This study of 15 teachers from rural, urban and suburban contexts in the US included ten who had been qualified for at least six years and so could be described as 'experienced' teachers [15]. Drewes [15] found that both novice and experienced teachers relied upon their agency as teachers that was rooted in their classroom practice to overcome periods of challenge and tension.…”
Section: Teacher Identity and Environmental And Sutstainability Educa...mentioning
confidence: 71%
See 4 more Smart Citations
“…These tensions and difficulties are also found in a more recent study of US-based high school science teachers who taught climate change using ESE-informed approaches [15]. This study of 15 teachers from rural, urban and suburban contexts in the US included ten who had been qualified for at least six years and so could be described as 'experienced' teachers [15]. Drewes [15] found that both novice and experienced teachers relied upon their agency as teachers that was rooted in their classroom practice to overcome periods of challenge and tension.…”
Section: Teacher Identity and Environmental And Sutstainability Educa...mentioning
confidence: 71%
“…Pedretti et al [14] suggest that these tensions are caused by the nascent development of the trainee teachers' professional identities which meant that it was more challenging to teach topics such as global warming and more difficult to teach science using ESE-informed approaches which are perceived by some as alternative or different to usual practice. These tensions and difficulties are also found in a more recent study of US-based high school science teachers who taught climate change using ESE-informed approaches [15]. This study of 15 teachers from rural, urban and suburban contexts in the US included ten who had been qualified for at least six years and so could be described as 'experienced' teachers [15].…”
Section: Teacher Identity and Environmental And Sutstainability Educa...mentioning
confidence: 88%
See 3 more Smart Citations